COST ACCOUNTING AND THE CLASSIFICATION OF MUNICIPAL EXPENDITURES. - Lorig, Arthur N. (The Accounting Review, 1936)
The article focuses on cost accounting and the classification of municipal expenditures. According to the author, financial accounting relates the expenditures to the various activities. Cost accounting goes further. It relates the expenditures to the amount of work done. Each activity is divisible into operations which, in turn, are measurable. The costs are first allotted to the activities or operations. The direct costs are chargeable directly; the indirect costs are necessarily apportioned to arrive at the true costs as accurately as careful estimation makes possible. The specific uses or purposes of municipal cost accounting help to indicate its nature. The information used in cost accounting comes for the most part from the general accounts. So intimately are they related that the cost accounting may and usually should be "tied in" with the general accounts. For the activities to which cost accounting is being applied, it is convenient to locate the detailed classification of expenditures by object in the cost accounts rather than the general accounts.